Contribution of online platform reservations to increase room occupancy at The Haven Hotel Bali Seminyak - Ayu Widya Wulandari; Budi Susanto; Ni Nyoman Triyuni; Ni Luh Ayu Kartika Yuniastari Sarja; I Ketut Budarma (Politeknik Negeri Bali, 2021)
This study discusses the contribution of online platform reservations to room occupancy rates at The Haven Hotel Bali Seminyak. The purpose of this study is to determine the contribution of online platform reservations to room occupancy rates and to find out which online platforms contributed the most. Data collection methods used are observation, interview, documentation. The analysis technique used is quantitative descriptive statistics. The results of this study stated that the contribution of the average percentage of online platforms for four years always fluctuates every year. Expedia for the last four years contributed 21.63% room occupancy rate, Booking.com for the last four years contributed 21.50% room occupancy rate, Agoda for the last four years contributed 10.66% room occupancy rate, Traveloka for four last year contributed 1.51% room occupancy rate, Hotelbed for the last four years contributed 2.14% room occupancy rate. Expedia contributed the most, viz 21.63% of room occupancy rate contribution for the last four years.